2019
DOI: 10.1016/j.jsams.2018.09.227
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness reference standards for preschool children: The PREFIT project

Abstract: on behalf of the PREFIT project group 2 a PROFITH "PROmoting FITness and Health through physical activity" a b s t r a c t Objectives: Reference values are necessary for classifying children, for health screening, and for early prevention as many non-communicable diseases aggravate during growth and development. While physical fitness reference standards are available in children aged 6 and older, such information is lacking in preschool children. Therefore, the purposes of this study were (1) to provide sex-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
80
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 32 publications
13
80
1
7
Order By: Relevance
“…The first finding from our study is that physical fitness levels were better in boys compared with girls, except for agility and flexibility, which agrees with results previously reported in children and adolescents . These differences may be attributed to the distinct development, growth, and maturation of boys and girls .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The first finding from our study is that physical fitness levels were better in boys compared with girls, except for agility and flexibility, which agrees with results previously reported in children and adolescents . These differences may be attributed to the distinct development, growth, and maturation of boys and girls .…”
Section: Discussionsupporting
confidence: 92%
“…For boys and girls, the performance in physical fitness tests increased with increasing age. While studies of adolescents have shown a stagnation or decrease in physical fitness with age, an improvement in physical fitness with increasing age is reported in children . Our results suggest that older children have better motor competency compared with young children.…”
Section: Discussionsupporting
confidence: 37%
See 2 more Smart Citations
“…Two sets of multivariate models were applied to investigate the relationships between preschoolers' step counts and physical fitness. Model 1 adjusted for no variables and Model 2 adjusted for potential confounding variables like BMI, a ge, a n d the accelerometer wear time [41,42].…”
Section: Discussionmentioning
confidence: 99%